175k views
3 votes
Show how
-1(x - 3)^2 + 4 is equal to
-x^2 +6x - 5

2 Answers

5 votes

Answer:

Explanation:

Expand:

-1(x^2-6x+9)+4=-x^2+6x-9 + 4 = -x^2 + 6x - 5

User Chris Ortiz
by
6.0k points
3 votes

Answer:

See Below.

Explanation:

We want to prove that:


-(x-3)^2+4=-x^2+6x-5

So, let’s expand the left side. This gives us:


=-(x-3)(x-3)+4

Distribute:


=-(x^2-3x-3x+9)+4

Simplify:


=-(x^2-6x+9)+4

Distribute:


=-x^2+6x-9+4

Simplify:


=-x^2+6x-5

Hence:


-(x-3)^2+4\stackrel{\checkmark}{=}-x^2+6x-5

User Ibelka
by
4.9k points